The beautiful Halal - Hashim, Yumi Zuhanis Has-Yun (TM-Info-Media Sdn. Bhd., 2010)
What we need is a credible system of certification where we can rest assured that a halal cosmetic is indeed halal, due to its halal raw/intermediates components.